Southeastern Coast of Bali Initial Risk Assessment. - PEMSEA; Bali PMO. (Quezon City, Philippines Bali Project Management Office, Denpasar, Bali, Indonesia and GEF/UNDP/IMO Regional Programme on Building Partnerships in Environmental Management for the Seas of East Asia (PEMSEA), 2004)
PEMSEA Technical Report no. 11